Proposing standard levels for some fitness elements according to a battery of tests to select young talents among handball players (17-19 years) - a field study on players of some of the states on the state handball association of setif - Belamri, yassine; bouali, lakhdar (sports creativity, 2025)
This study dealt with the topic of "suggesting standard levels for some elements of physical fitness according to a battery of tests to select young talents in handball", a field study conducted on the players of some of the state handball league teams Sétif - Algeria. The objective of this study included suggesting standard levels according to the characteristics of the study community Including selection in order to build a talented athletic model through standard physical levels that assist coaches in selecting young talents in handball, and this is based on the descriptive approach in the survey method. The research sample included 54 of the category (17-19 years) who were chosen intentionally from the study community The information was used to collect a proposed physical test battery and then statistically processed its results using standard scores to classify the sample members into six grades from weak to excellent, and the results of the study recommended the use of the proposed levels, which are scientific support for the field observation to facilitate the selection process